A k‐nearest neighbor query method based on trust and location privacy protection. (6th April 2020) - Guo, Liangmin; Zhu, Ying; Yang, Hao; Luo, Yonglong; Sun, Liping; Zheng, Xiaoyao
Abstract: Spatial query is an important supporting technology in the Internet of Things (IoT) and location‐based services (LBS). The k ‐nearest neighbor query is widely used for spatial queries. However, user location privacy may be leaked in the query. In addition, some users are malicious or uncooperative. With the objective of overcoming these problems, a k ‐nearest neighbor query method based on trust and location privacy protection is proposed. First, we employ a new K ‐anonymity method based on cooperation to protect a query user's location privacy. In this method, the query user constructs an anonymous group by introducing a trust mechanism to incentivize cooperation among users. Then, according to the different radii of the selection area set by the query user, agent users with higher reputation values who send query requests for the query user are selected. Finally, the agent users obtain the query results from the LBS server and forward them to the query user, and the query user screens the results according to his or her real location. The experiments show that our method can effectively stimulate users to cooperate, better exclude malicious users, and improve the accuracy of the query results while protecting the privacy of the query user.